Exiting from Fragility in Sub‐Saharan Africa: The Role of Fiscal Policies and Fiscal Institutions. (27th April 2018) - Deléchat, Corinne; Fuli, Ejona; Mulaj, Dafina; Ramirez, Gustavo; Xu, Rui
Abstract: This paper studies the role of fiscal policies and institutions in building resilience in sub‐Saharan African countries, focussing on 26 countries that were deemed fragile in the 1990s. We use a probabilistic framework together with GMM estimation to address endogeneity and reverse causality. We find that fiscal institutions and fiscal space, namely the capacity to raise tax revenue and contain current spending, as well as the quality of public expenditure, are significantly and robustly associated with building resilience. Similar conclusions arise from a qualitative study of 7 sub‐Saharan African countries in the sample that built resilience since the 1990s.